2009
DOI: 10.1002/ptr.2901
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity and antigenotoxicity evaluation of non‐photoactivated hypericin

Abstract: The potential genotoxicity and antigenotoxicity of non-photoactivated hypericin was investigated in five experimental models. Hypericin was non-mutagenic in the Ames assay, with and without metabolic activation. It did not exert a protective effect against mutagenicity induced by 9-aminoacridine. In a yeast (Saccharomyces cerevisiae) assay, hypericin did not increase the frequency of mitotic crossovers or total aberrants at the ade(2) locus, the number of convertants at the trp5 locus, or the number of reverta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
19
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 19 publications
4
19
0
1
Order By: Relevance
“…They found out that non-photoactivated HYP was not mutagenic. In our previous paper (Miadokova et al 2010) we have shown that none of the concentrations of non-photoactivated HYP exerted mutagenic effects on strain TA97. Now we present the results of the Ames/Salmonella typhimurium assay on 3 bacterial strains (TA 97, TA 98 and TA100).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…They found out that non-photoactivated HYP was not mutagenic. In our previous paper (Miadokova et al 2010) we have shown that none of the concentrations of non-photoactivated HYP exerted mutagenic effects on strain TA97. Now we present the results of the Ames/Salmonella typhimurium assay on 3 bacterial strains (TA 97, TA 98 and TA100).…”
Section: Discussionmentioning
confidence: 87%
“…The Williams medium was supplemented with gentamicin (50 μg/ml) (Sandoz, Slovenia). The cells were cultured in plastic Petri dishes in CO 2 /air (5%: 95%) environment at 37°C, as previously described by Miadokova et al (2010).…”
Section: Experimental Cells and Cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among others it possesses properties suitable for PDT (Čavarga et al, 2005;Chan et al, 2009) and PDD (Thong et al, 2009). Peculiar attributes of this photosensitizer are high efficiency in production of singlet oxygen (Redmond & Gamlin, 1999) and superoxide anions after irradiation with light wavelength around 600 nm and low or no toxicity in the dark (Jacobson et al, 2001;Miadoková et al, 2009). Photoactivated HY is known to induce changes at cellular as well as vascular level or even affect CD8+ T cell-mediated cytotoxicity (Lavie et al, 2000).…”
Section: Hypericinmentioning
confidence: 99%
“…For genotoxicity/antimutagenicity assay eukaryotic test system S. cereviviae D7 was used. This mutant yeast strain was constructed to simultaneous testing of toxicity, reverse mutations in ilv1 locus, mitotic crossing-over and total aberrations at the ade2 locus and mitotic gene conversion at the trp5 locus (ZIMMERMANN et al, 1984;VLCKOVA et al, 2006;MIADOKOVA et al, 2010).…”
mentioning
confidence: 99%